2001
DOI: 10.1007/s002130000661
|View full text |Cite
|
Sign up to set email alerts
|

Treatment regimen and hypnotic self-administration

Abstract: The data of this study are consistent with the view that hypnotic self-administration by insomniacs is therapy-seeking behavior and not drug abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…Non-nightly treatment regimens have been suggested due to concerns in regard to tolerance development and the development of physical/ behavioral dependence. As previously noted, tolerance does not readily develop, physical dependence is not observed, and a non-nightly treatment regimen did not alter the likelihood of behavioral dependence in a short-term study [95]. There is no clear advantage to non-nightly treatment regimens, at least in regard to the risks of tolerance or abuse.…”
Section: Specific Nature Of Insomnia and Patient Characteristicsmentioning
confidence: 61%
“…Non-nightly treatment regimens have been suggested due to concerns in regard to tolerance development and the development of physical/ behavioral dependence. As previously noted, tolerance does not readily develop, physical dependence is not observed, and a non-nightly treatment regimen did not alter the likelihood of behavioral dependence in a short-term study [95]. There is no clear advantage to non-nightly treatment regimens, at least in regard to the risks of tolerance or abuse.…”
Section: Specific Nature Of Insomnia and Patient Characteristicsmentioning
confidence: 61%
“…In the only study with adequate data for meta-analysis, Roehrs 96 found a small reduction in subjective SL (−9.2 min; CI: −22.3 to +3.9 min) which fell below clinical significance. Quality of evidence for these data was high.…”
Section: Sleep Latencymentioning
confidence: 88%
“…Because only one study 96 contained data of sufficient quality, meta-analysis was not performed. The quality of evidence for this study was high.…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong placebo effect in insomnia patients and they self-administer capsules, whether placebo or active drug, on 60% to 80% of nightly opportunities. Another recent short-term study sought to determine whether an 11-night intermittent treatment instruction compared with a nightly bedtime and an as required instruction would alter the subsequent likelihood of self-administering a hypnotic (triazolam, 0.25 mg) over a 1-week free-choice period [10]. Experience with the prior intermittent treatment (ie, capsules every third night) did not alter subsequent drug taking compared with prior nightly dosing at bedtime or the as necessary at bedtime instruction.…”
Section: Chronic Use In Chronic Insomniamentioning
confidence: 99%